Biological Control Efficacy and Action Mechanism of Klebsiella pneumoniae JCK-2201 Producing Meso-2,3-Butanediol Against Tomato Bacterial Wilt - Kim, Bora; Park, Ae Ran; Song, Chan Woo; Song, Hyohak; Kim, Jin-Cheol (Frontiers in Microbiology, 2022)
Bacterial wilt caused by Ralstonia solanacearum is a fatal disease that affects the production of tomatoes and many other crops worldwide. As an effective strategy to manage bacterial wilt, biological control agents using plant growth-promoting rhizobacteria (PGPR) are being developed. In this study, we screened 2,3-butanediol-producing PGPR to control tomato bacterial wilt and investigated the action mechanism of the disease control agent. Of the 943 strains isolated from soil, Klebsiella pneumoniae strain JCK-2201 produced the highest concentration of 2,3-butanediol (BDO). The culture broth of K. pneumoniae JCK-2201 did not show any direct activity on R. solanacearum in vitro, but a 100-fold dilution effectively controlled tomato bacterial wilt with a control value of 77% in vivo. Fermentation utilizing K. pneumoniae JCK-2201 was optimized to produce 48 g/l of meso-2,3-BDO, which is 50% of the sucrose conversion efficiency. In addition, the control efficacy and mechanism of meso-2,3-BDO produced by JCK-2201 in tomato bacterial wilt were determined by comparative analysis with Bacillus licheniformis DSM13 producing meso-2,3-BDO and B. licheniformis DSM13 △alsS that did not produce 2,3-BDO, as the step of converting pyruvate to α-acetolactate was omitted. Tomato seedlings treated with the K. pneumoniae JCK-2201 (500-fold dilution) and B. licheniformis DSM13 (100-fold dilution) culture broth produced meso-2,3-BDO that significantly reduced R. solanacearum-¬induced disease severity with control values of 55% and 63%, respectively. The formulated meso-2,3-BDO 9% soluble concentrate (SL; 1,000-fold dilution) showed 87% control against tomato bacterial wilt in the field condition. JCK-2201 and DSM13 treatment induced the expression of plant defense marker genes, such as LePR1, LePR3, LePR5, LePR3, and PI-II, in the salicylic acid and jasmonic acid signaling pathways at 4 days after inoculation. These results show that 2,3-BDO-producing bacteria and 2,3-BDO are potential biological control agents that act through induction of resistance for controlling tomato bacterial wilt.